FIKIH TEACHER PEROFESIONALISM IN THE IMPLEMENTATION OF TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) AT MTS NW SENYIUR - amriyogi ardiyansah (Sinar Lima, 2024)
The TPCK model is a useful tool for characterizing and evaluating teachers' technology integration skills. This research aims to describe the skills or professionalism of Fiqh teachers in the implementation of Technological Pedagogical Content Knowledge (TPCK) in Fkih learning at MTs NW Senyiur. This research uses a qualitative approach. The data analysis techniques, namely data collection (data reduction), data display (data display) as well as drawing conclusions and verification. Based on the results of this research, it shows that: 1) Technological Knowledge (TK) of teachers in learning jurisprudence in Class VIII, namely a) using hardware such as laptops, LCD projectors, and b) using software such as Microsoft Word, Microsoft Excel, and Microsoft Power Point ; 2) Pedagogical Knowledge (PK) of teachers in learning jurisprudence in Class VIII; a) Class management by conditioning students before learning activities and applying interesting learning methods; b) Learning planning by preparing syllabus, lesson plans and power point media; c) Carrying out learning activities in three stages, namely preliminary activities, core activities and closing; d) Evaluate learning with three aspects, namely attitudes, knowledge and skills; 3) The teacher's Content Knowledge (CK) in class VIII fiqh learning includes: a) content knowledge, which is demonstrated by using various learning resources; b) explanation of the material using the lecture method using PowerPoint presentations; and c) examples that are appropriate to the material discussed in class, such as pictures and videos.